COMMUNICATION OF BAD NEWS IN HEALTH PROFESSIONAL TRAINING - Raphael Almeida Ribeiro, Thiago; Paula de Oliveira Santos, Ana; Ribeiro Almeida, Dannyelle; Heineck, Raíssa; Silva Pereira, Alessandra; Medawar Leão, Harley; Xavier da Silva, Rosilaine; Siega Nepomuceno, Matheus; Lécia Gonçalves de Andrade, Weslaine; Sérgio David de Castro, Paulo; Souza Santos de Sá, Daniela; Guimarães da Silva, Aline; et al. (Health and Society, 2026)
The present study aims to understand the process of communicating bad news in the training of healthcare professionals. A theoretical-reflective study was conducted based on the concepts of health education and health promotion. It was evidenced that current training often provides limited theoretical support and few opportunities for simulated or supervised practice in handling the communication of bad news. This results in professionals who, although technically capable, feel insecure and unprepared to deal with the emotional burden and ethical implications of these interactions. The present study achieved its overall objective by understanding and analyzing the process of communicating bad news as addressed and experienced in the training of healthcare professionals. The findings highlight the critical importance of integrating this fundamental competency more systemically and thoroughly into the area’s curricula.